Regulation of the Governor of Southeast Sulawesi Number 37 of 2020 concerning Amendments to Governor Regulation Number 9 of 2020 on Healthy Southeast Sulawesi Regional Health Insurance: A MOST Analysis Approach - Waode Sitti Nurrokhmadani; Andi Rini Indriani Saedah; Sariyanti; Yuli Solihati (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Equitable and high-quality access to health services is a key priority for regional governments. In Southeast Sulawesi, the Healthy Southeast Sulawesi Regional Health Insurance Program was established to provide health coverage for communities not yet included in the national health insurance scheme. To improve this program, the Governor of Southeast Sulawesi issued Regulation Number 37 of 2020, which amended Regulation Number 9 of 2020. This amendment aimed to strengthen administrative systems, financial governance, and supervisory mechanisms in the implementation of regional health insurance. Objective: This study aims to analyze the implementation of Governor Regulation Number 37 of 2020 using the MOST (Mission, Objectives, Strategy, Tactics) framework to assess the policy’s effectiveness and recommend areas for improvement. Method: The research uses a qualitative descriptive method through literature review. Data sources include the Governor Regulation and supporting documents. The MOST framework is applied to examine the internal structure and strategic approach of the policy. Results: The regulation introduces several strategies to enhance transparency and efficiency in managing regional health insurance funds. However, its effectiveness depends on adequate supervision, strong administrative support, and coordination among stakeholders. Conclusion: Governor Regulation Number 37 of 2020 is a strategic step toward equitable health service access. Its success requires strengthened institutional capacity, better interagency coordination, and continuous evaluation. Keywords: Regional Health Insurance, Health Policy, MOST Analysis, Health Financing, Southeast Sulawesi